Bridging self and the research, researching and communicating - Haji Masud, Faizah (Institute of East Asian Studies and Universiti Malaysia Sarawak, 2013)
The discussion will revisit the importance and benefits of Insider-Outsider Perspectives for researchers researching Malaysian topics within a Malaysian context. In qualitative or quantitative approaches, research is not only researching and producing findings, but also a process in which the researcher is involved in making decisions, analyzing and interpreting information and results. However, in this chapter, I will focus on the qualitative approach because unlike quantitative method, qualitative research deals with emotion, values, and the complexity of human beings by exploring and interpreting social phenomena as experienced by individuals themselves in the natural setting (Smythe, 2012). Here, I will discuss self-reflection from the insider-outsider perspectives as critical in carrying out rigorous and significant research on local topics. A researcher focusing on Malaysia will enter the research field of study with preconceptions of personal beliefs, knowledge and unique experiences and perceptions on the subject of the research and the world which is manifested throughout the research process. I believe as Malaysian or non-Malaysian, self reflection or the insider-outsider’s perspectives will provide researchers with comprehensive input to select appropriate, reliable, clear and comprehensive methodological and theoretical frameworks to interpret and analyze information from the research.